Językoznawczy kontekst badań edukacyjnych - Wiśniewska-Kin, Monika (Studia Edukacyjne, 2020)
The article is going to show how the approach to the educational role of language has changed. The emergence of new thinking about language is directly associated with the tendency to shift from objectivity to subjectivity. To make the reconstruction of this change, I will discuss the selected elements of the structuralist theory of language and compile them with elements of the cognitive theory of language; for instance, classic categorization methods vs. natural categorization, taxonomic definingvs. cognitive defining.The proposed comparative analyzes open up space to thinking about the measures that can be taken in order to create conditions conducive to revealing the real development potential of a child in the process of education.